COMPARATIVE CYTOGENETIC STUDY AMONG PARACHANNA OBSCURA POPULATIONS FROM SELECTED WATER BODIES IN SOUTH WEST, NIGERIA - Ekundare, Olugbemi Victor; Fagbuaro, Omotayo (FUDMA Journal of Sciences, 2024)
Parachanna obscura is a freshwater Perciform species that belong to the family Channidae. In contrast to many other fish species, the genetic information about P. obscura as a species is very scarce and its chromosome compliments in different confined populations all over remain undiscovered. In view of this, this study considered the cytogenetic variations among three populations of P. obscura collected from River Elemi, Ado-Ekiti, Ekiti State, Egbe-Ekiti Reservoir, Egbe, Ekiti State and Esa-Odo Reservoir, Esa-Odo, Osun State, Nigeria. Each sampled fish was injected with 0.05% Colchicines solutions (1.0ml/kg), metaphase chromosome spread were made from the head kidney of each sample. Slides were prepared using conventional Giemsa staining method while digital images of the metaphase spreads were taken. Study revealed that all P. obscura from the three different population has the same diploid chromosome number 2n=46. The chromosome length range from River Elemi, Ado-Ekiti (6.10-14.91 µm), Egbe water reservoir, Egbe-Ekiti (5.91-16.06 µm) and Esa-odo water reservoir, Esa-Odo (6.24-14.31 µm), were very close thus exhibiting homomorphic character with respect to total length. Karyotypic formula differs among populations of River Elemi, Ado-Ekiti (2n= 2sm + 44t), Egbe water reservoir, Egbe-Ekiti (2n=4sm + 2st + 40t) and Esa-odo water reservoir, Esa-Odo (2n=2st + 44t), this implies that the three populations were navigating different evolutionary course resulting from fragmentation and isolation of populations. In conclusion further molecular cytogenetic studies may add more to the view presented in this study.
Keywords: P. obscura; Chromosomes; Karyotype; Metaphase spread; Cytogenetics